2022
DOI: 10.3390/ijerph19074154
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Transformation and Urban Economic Efficiency Evolution: An Empirical Study of the Yangtze River Economic Belt

Abstract: Industrial transformation and high-quality urban development have become the core issues of urban-rural coordination and the leap forward in development in the new era. The research perspective of ‘pattern-process-mechanism’ is needed to reveal the spatiotemporal correlation characteristics of industrial transformation and urban economic efficiency evolution, and to expand its systematic, comprehensive and regional characteristics. Based on the geographical cognitive of local effects and spatial non-stationari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Deng et al, 2019). As environmental regulation intensity increases, the enthusiasm of enterprises to migrate to the area gradually declines, which will not be conducive to the diversified development of industries in the region (Dong & Zhang, 2020). In addition, as environmental regulation intensity increases, enterprises with high energy consumption and high pollution are forced to move to regions with lower environmental regulation intensity, thus forming a “pollution refuge.” Although these enterprises can increase local output to some extent, they do not improve the local production technology and operating environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deng et al, 2019). As environmental regulation intensity increases, the enthusiasm of enterprises to migrate to the area gradually declines, which will not be conducive to the diversified development of industries in the region (Dong & Zhang, 2020). In addition, as environmental regulation intensity increases, enterprises with high energy consumption and high pollution are forced to move to regions with lower environmental regulation intensity, thus forming a “pollution refuge.” Although these enterprises can increase local output to some extent, they do not improve the local production technology and operating environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A series of regional integration policies based on the strategic framework of regional synergistic development guide formal or informal institutional cooperation and serve as a spatial blueprint for sustainable regional development [17]. China has now proposed several regional economic development visions and implemented a series of regional development strategies, such as the Western Development Strategy [18], the Yangtze River Economic Belt Development [19], the Guangdong-Hong Kong-Macao Greater Bay Area Construction [20], and the BTH synergistic development [21]. Studies have shown that regional synergistic development strategies are conducive to enhancing economic ties within urban agglomerations [17], upgrading regional industrial structures, breaking down administrative barriers within regions [22], optimising spatial structures, and promoting optimal allocation and free flow of production factors within regions [23].…”
Section: Introductionmentioning
confidence: 99%